Space in tourism, tourism in space: on the need for definition, delimitation and classification - Włodarczyk, Bogdan (Turyzm/Tourism, 2014)
Tourism space has been considered by most researchers to be the central object of tourism geography studies. The author defines tourism space, indicating the features which distinguish it within geographical space, as well as those which describe its character. He also presents a discussion on the need (or necessity) to make internal divisions and classifications, as well as on selected criteria and ways of classifying tourism space.